Prevalence and structural correlates of gender based violence among a prospective cohort of female sex workers. (11th August 2009) - Shannon, Kate; Kerr, T; Strathdee, S A; Shoveller, J; Montaner, J S; Tyndall, M W
Abstract : Objective To examine the prevalence and structural correlates of gender based violence against female sex workers in an environment of criminalised prostitution. Design Prospective observational study. Setting Vancouver, Canada during 2006-8. Participants Female sex workers 14 years of age or older (inclusive of transgender women) who used illicit drugs (excluding marijuana) and engaged in street level sex work. Main outcome measure Self reported gender based violence. Results Of 267 female sex workers invited to participate, 251 women returned to the study office and consented to participate (response rate of 94%). Analyses were based on 237 female sex workers who completed a baseline visit and at least one follow-up visit. Of these 237 female sex workers, 57% experienced gender based violence over an 18 month follow-up period. In multivariate models adjusted for individual and interpersonal risk practices, the following structural factors were independently correlated with violence against female sex workers: homelessness (adjusted odds ratio for physical violence (aORphysicalviolence ) 2.14, 95% confidence interval 1.34 to 3.43; adjusted odds ratio for rape (aORrape ) 1.73, 1.09 to 3.12); inability to access drug treatment (adjusted odds ratio for client violence (aORclientviolence ) 2.13, 1.26 to 3.62; aORphysicalviolence 1.96, 1.03 to 3.43); servicing clients in cars or public spaces (aORclientviolence 1.50, 1.08 to 2.57); prior assault by police (aORclientviolence 3.45, 1.98 to 6.02; aORrape 2.61, 1.32 to 5.16); confiscation of drug use paraphernalia by police without arrest (aORphysicalviolence 1.50, 1.02 to 2.41); and moving working areas away from main streets owing to policing (aORclientviolence 2.13, 1.26 to 3.62). Conclusions Our results demonstrate an alarming prevalence of gender based violence against female sex workers. The structural factors of criminalisation, homelessness, and poor availability of drug treatment independently correlated with gender based violence against street based female sex workers. Socio-legal policy reforms, improved access to housing and drug treatment, and scale up of violence prevention efforts, including police-sex worker partnerships, will be crucial to stemming violence against female sex workers.